STUDI AWAL DAMPAK PERUBAHAN IKLIM BERBASIS ANALISIS VARIABILITAS CO2 DAN CURAH HUJAN (Studi Kasus; Semarang Jawa Tengah) - Gernowo, Rahmat; Adi, Kusworo; Arifin, Zaenal (BERKALA FISIKA, 2012)
Impacts of climate change marked by the increasing emissions of CO2 in the air and increasedÂ precipitation make various parties began to feel the need to measure the gas content on a regular basis.These gases gradually accumulating in Earth's atmospheric layers. However, the desire was constrainedby a number of issues which then affect the accuracy of the continuous mapping circulating gas in theatmosphere. Researchers speculate that the amount of CO2 and other gases is growing each day due tothe many additional human-produced carbon emissions from burning fossil fuels. The results obtained bythe pattern of variability in Semarang rising CO2 and rising precipitation trends show an indication ofclimate change has occurred. It was proven occurrence of climate anomalies and the previous year.Keywords: CO2 variability, Rainfall Semarang